PENERAPAN SISTEM PENCARIAN ABSTRAK JURNAL BERDASARKAN KATA KUNCI MENGGUNAKAN ALGORITMA NAIVE BAYES (STUDI KASUS : ABSTRAK JURNAL STMIK BANDUNG) - Deddy Apriadi; Haris Irnawan; Syiffa Nurjayanti (LPPM STMIK BANDUNG, 2022)
Document search is a search activity effort to produce the information sought. Along with the development of effective technology used and in presenting detailed information, consumer needs for information in the form of journals or scientific articles are increasing. Naive Bayes is a data mining algorithm in searching for text patterns, this algorithm can help document search by applying the k-gram method, document extraction, and similarity values as well as extreme programming as a software development method, to assist in searching (journal abstract) based on keywords.